Holding the therapeutic state at bay? Balancing autonomy and protection in Singapore's Vulnerable Adults Act - CHAN, Wing Cheong (Institutional Knowledge at Singapore Management University, 2020)
Abuse, exploitation and neglect of adults raise complex issues on the freedom of the individual to choose for themselves versus the powers of the State to intervene. The law has traditionally limited the scope of compulsory intervention to extreme situations only which can frustrate social workers who deal with such cases. On the other hand, it would be unacceptable to allow intervention simply because it is assessed to be in the adults’ best interests. A balance therefore has to be struck between autonomy and protection. This paper examines how Singapore’s Vulnerable Adults Act identifies the point for intervention and embodies safeguards to prevent abuse of the State’s powers.